(untitled) (Polis (Santiago), 2018)
The author argues that in the beliefs of indigenous societies there is no concept of development, less as something to undertake by people in order to achieve well-being; nor the concepts of wealth and poverty determined by accumulation and lack of material goods. There does exist an holistic view about what should be the goal or mission of every human effort, which is to find and create material and spiritual conditions for building and maintaining an "harmonious life". This places sustainability under a different paradigm which incorporates transcendence and the spirituality.